Deciphering the Origin of Abiotic Organic Compounds on Earth: Review and Future Prospects - WANG, Chao; TAO, Renbiao; WALTERS, Jesse B.; REN, Tianshi; NAN, Jingbo; ZHANG, Lifei (Acta geologica Sinica (Beijing), 2023)
The geologic production of abiotic organic compounds has been the subject of increasing scientific attention due to their use in the global carbon flux balance, by chemosynthetic biological communities, and for energy resources. Extensive analysis of methane (CH4) and other organics in diverse geologic settings, combined with thermodynamic modelings and laboratory simulations, have yielded insights into the distribution of specific abiotic organic molecules on Earth and the favorable conditions and pathways under which they form. This updated and comprehensive review summarizes published results of petrological, thermodynamic, and experimental investigations of possible pathways for the formation of particular species of abiotic simple hydrocarbon molecules such as CH4, and of complex hydrocarbon systems, e.g., long‐chain hydrocarbons and even solid carbonaceous matters, in various geologic processes, distinguished into three classes: (1) pre‐ to early planetary processes; (2) mantle and magmatic processes; and (3) the gas/water‐rock reaction processes in low‐pressure ultramafic rock and high‐pressure subduction zone systems. We not only emphasize how organics are abiotically synthesized but also explore the role or changes of organics in evolutionary geological environments after synthesis, such as phase transitions or organic‐mineral interactions. Correspondingly, there is an urgent need to explore the diversity of abiotic organic compounds prevailing on Earth.